Movers and stayers: The geography of residential mobility and CVD hospitalisations in Auckland, New Zealand. (May 2015) - Exeter, Daniel J.; Sabel, Clive E.; Hanham, Grant; Lee, Arier C.; Wells, Susan
Abstract: The association between area-level disadvantage and health and social outcomes is unequivocal. However, less is known about the health impact of residential mobility, particularly at intra-urban scales. We used an encrypted National Health Index (eNHI) number to link individual-level data recorded in routine national health databases to construct a cohort of 641, 532 participants aged 30+ years to investigate the association between moving and CVD hospitalisations in Auckland, New Zealand. Residential mobility was measured for participants according to changes in the census Meshblock of usual residence, obtained from the Primary Health Organisation (PHO) database for every calendar quarter between 1/1/2006 and 31/12/2012. The NZDep2006 area deprivation score at the start and end of a participant's inclusion in the study was used to measure deprivation mobility. We investigated the relative risk of movers being hospitalised for CVD relative to stayers using multi-variable binomial regression models, controlling for age, gender, deprivation and ethnicity. Considered together, movers were 1.22 (1.19–1.26) times more likely than stayers to be hospitalised for CVD. Using the 5 × 5 deprivation origin-destination matrix to model a patient's risk of CVD based on upward, downward or sideways deprivation mobility, movers within the least deprived (NZDep2006 Quintile 1) areas were 10% less likely than stayers to be hospitalised for CVD, while movers within the most deprived (NZDep2006 Q5) areas were 45% more likely than stayers to have had their first CVD hospitalisation in 2006–2012 (RR: 1.45 [1.35–1.55]). Participants who moved upward also had higher relative risks of having a CVD event, although their risk was less than those observed for participants experiencing downward deprivation mobility. This research suggests that residential mobility is an important determinant of CVD in Auckland. Further investigation is required to determine the impact moving has on the risk of CVD by ethnicity. Highlights: This is the first study of migration and health in NZ using record linkage. Movers were more likely to have CVD events than stayers. Risk of CVD risk is lower for upwardly mobile than downwardly-mobile. Risk among movers within the most deprived areas was 45% higher than stayers. The most deprived areas have the highest CVD risk, regardless of move direction.